Ecotoxicological effects of fipronil, neem cake and neem extract in edaphic organisms from tropical soil - Zortea T.* (2018)
© 2018 Elsevier Inc.Veterinary medicines are widely applied for the treatment and prevention of animal diseases. Consequently, animal manure contains significant amounts of environmental pollutants that are potential sources of environmental pollution when inappropriately applied in soils. This work aimed to evaluate ecotoxicological effects of doses of commercial fipronil, neem cake and neem extract in the survival and reproduction of earthworms (Eisenia andrei), enchytraeidae (Enchytraeus crypticus) and springtails (Folsomia candida) in Oxisol and tropical artificial soil (TAS). Applications of fipronil, neem cake and extract in soil were carried out according to standardized ISO methodologies by using a random experimental design with five replicates. Toxic effects of fipronil for springtails in Oxisol and TAS were observed with LC50 of 0.26 mg kg−1 (0.18–0.35 mg kg−1) and 0.29 mg kg−1 (0.22–0.37 mg kg−1), respectively. It was not observed significant toxic effects of fipronil for earthworms and enchytraeidae in both soils. However, significant amounts of juvenile earthworm and adult enchytraeidae decreased in fipronil doses higher than 10 mg kg−1. Neem cake and extract were not toxic for earthworms and enchytraeidae but, significant amounts of juvenile springtails decreased in neem cake doses from 500 to 1000 mg kg−1. It can be concluded that the use of veterinary medicines containing synthetic compounds for preventing diseases in animals needs to be controlled to avoid environmental pollution after applying manure in soil. Veterinary medicines containing natural compounds as neem cake and extract are eco-friendly and could be efficiently applied in soil in a sustainable way.